Using mixed methods to explore diabetes care in a medium‐secure setting in England: A case study. Issue 4 (14th December 2021) - Walker, Tammi; Edmondson, Amanda; Riley, Fleur; Harper, Mark; Lucock, Mike; Wright, Nat
Abstract: Background and aims: Diabetes is highly prevalent among individuals with serious mental illness. Managing diabetes in forensic mental health settings presents unique challenges which are under‐reported and poorly understood. This study aimed to explore diabetes care in a medium‐secure setting and identify key areas for improvement. Methods: A single case study design used a retrospective chart review. Qualitative interviews and a focus group were analyzed using thematic analysis. Results: Prevalence of diabetes was over twice that of the general population and highest in female service users. Evidence suggests limited understanding and lack of diabetes education for staff and service users, and difficulties in accessing external diabetes recourses. Conclusion: Constraints inherent to forensic mental health settings contribute to difficulties in accessing external resources and adequate diabetes education. Secure mental health services should adopt a collaborative approach to diabetes care and provide appropriate specialist training to both staff and service users.